Traumatic axonal injury successfully treated with secretome followed by mesenchymal stem cells therapy - Ahmad Faried; Yeremia Tatang; Gibran A. Wibawa; Wahyu Widowati; Anindita P. Distya (European Journal of Case Reports in Internal Medicine)
Introduction: Traumatic axonal injury (TAI), a head injury condition formerly known as diffuse axonal injury, results from direct mechanical forces causing multiple scattered lesions, either haemorrhagic or non-haemorrhagic, within brain tissue. Despite its clinical significance, no prior research has explored the use of stem cells in a TAI inpatient setting. This case presents the efficacy of stem cell therapy for TAI. Case description: A 17-year-old boy sustained severe head injuries from repeated blows, resulting in a coma. Initial CT and MRI scans showed cerebral oedema without haemorrhagic lesions. T2-weighted axial FLAIR imaging showed two hyperintensity lesions in the corpus callosum, consistent with diffuse axonal injury grade II. Secretome and umbilical cord mesenchymal stem cell (UCMSC) therapy were administered. The patient showed improvement in motor function and speaking and was discharged without neurological deficits. Discussion: The pathophysiology of TAI remains unclear because of a lack of unifying theory. It is theorised that not only is direct mechanical injury the cause of primary damage but biochemical changes in neuronal metabolism also play a role as secondary damage. Two main therapeutic options can be recognised. Treatment approaches fall into two categories: secondary axotomy-targeted therapy and promotion of neural regeneration. Multiple treatment options promote both microenvironment correction and neuronal regeneration, including cell and stem cell therapy along with its metabolite. Conclusion: Stem cell therapy is promising as an alternative treatment modality in a case where there was no other optional therapy for TAI.